The Effects of Health Related Fitness Awareness on Physical Activity Among School Students (Journal of Asian Development Studies, 2023)
This study aims to investigate the effects of health-related fitness awareness on physical activity among school students. The quantitative research technique was applied to gather the information from the participants. A total of 180 boys and girls aged between 13 and 16 years school students were selected for the study. The data was collected from the school students of district Bahawalpur. The researcher employed convenient sampling as the sampling technique for the particular analysis. The researcher used a questionnaire as a research tool to collect data on health-related fitness awareness in numeric form from the research participants. The results were analysed through quantitative research tools, i.e., descriptive statistics, t-tests, bivariate correlation, and regression analysis in SPSS. The findings revealed a positive correlation between students' health-associated fitness awareness and bodily pursuit. Linear regression analysis demonstrated that health-related fitness awareness significantly predicted PA among the students. The results revealed a significant difference (p < .01) between the health-related fitness awareness scores of boys (M = 8.85, SD = 1.78) and girls (M = 8.4, SD = 1.73). This finding indicated that boys had higher health-related fitness awareness scores than girls. The study concluded that promoting health-related fitness awareness may increase PA levels among school students.